Fossil quality and naming dinosaurs - Benton, Michael J (The Royal Society, 2008)
The intense interest in dinosaurs through the past 30 years might have led to an increase in poor practice in naming new species. A review of the data shows that the reverse is the case. For 130 years, from the 1820s to the 1950s, most new species of dinosaurs were based on scrappy and incomplete material. After 1960, the majority of new species have been based on complete skulls or skeletons, and sometimes on materials from several individuals. This switch in the quality of type specimens corresponds to the recent explosive renaissance of interest in dinosaurs, during which the number of new species named per year has risen, from three or four in the 1950s, to thirty or more today. The pattern of specimen quality varies by continent, with the highest proportion of new species based on good material in North America, then Asia, then South America, then Africa and finally Europe. This ranking reflects a complex pattern of perhaps overstudy in Europe, immensely rich reserves of new dinosaur materials in North America and Asia, and a relative paucity in South America and Africa.